2022
DOI: 10.1101/2022.02.27.22271090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Rapid Antigen Tests’ Performance between Delta (B.1.61.7; AY.X) and Omicron (B.1.1.529; BA1) Variants of SARS-CoV-2: Secondary Analysis from a Serial Home Self-Testing Study

Abstract: Background: There is a need to understand the performance of rapid antigen tests (Ag-RDT) for detection of the Delta (B.1.61.7; AY.X) and Omicron (B.1.1.529; BA1) SARS-CoV-2 variants. Methods: Participants without any symptoms were enrolled from October 18, 2021 to January 24, 2022 and performed Ag-RDT and RT-PCR tests every 48 hours for 15 days. This study represents a non-pre-specified analysis in which we sought to determine if sensitivity of Ag-RDT differed in participants with Delta compared to Omicron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…911 To investigate concerns that RATs may have inferior performance for Omicron versus Delta infections, a study compared same-day positivity between the variants, finding similar sensitivity of RAT and PCR tests. 12 Lastly, RATs have the advantage of relative affordability, fast turnaround time, and at-home self-administration compared to PCR, making them the only viable exit test option for much of the population. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…911 To investigate concerns that RATs may have inferior performance for Omicron versus Delta infections, a study compared same-day positivity between the variants, finding similar sensitivity of RAT and PCR tests. 12 Lastly, RATs have the advantage of relative affordability, fast turnaround time, and at-home self-administration compared to PCR, making them the only viable exit test option for much of the population. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] To investigate concerns that RATs may have inferior performance for Omicron versus Delta infections, a study compared same-day positivity between the variants, finding similar sensitivity of RAT and PCR tests. 12 Lastly, RATs have the advantage of relative affordability, fast turnaround time, and at-home self-administration compared to PCR, making them the only viable exit test option for much of the population. 13,14 To address the evidence gaps regarding optimal isolation durations and how SARS-CoV-2-positive persons can best utilize exit RATs when resources are limited, we evaluated daily RAT data from 324 persons in a university-managed isolation program who initially tested positive for SARS-CoV-2 between January 1 and February 11, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…This result provided important information regarding our ability to implement BinaxNOW TM , antigen-based testing, as a surrogate for qRT-PCR testing. A cutoff value of 24 for qRT-PCR is below the average C T value reported for both delta and omicron variants (5,6,8,9,12,13), suggesting that RDT testing alone would be insufficient to maintain control of spread in our community (Supplementary Table 3). Thus, the conclusion of our qualification study was that it is not possible to use the BinaxNOW TM test alone to replace qRT-PCR in our testing sites for ruling-out positive individuals.…”
Section: Discussionmentioning
confidence: 93%
“…These studies suggested that there was analytical strength in the RDT, but also suggested a limited range of viral loads in which the assays consistently returned positive results from PCR positive samples. Two additional studies look at a broader range of SARS-CoV-2 RDT tests include a 15-day study of individuals with no symptoms comparing delta and omicron on 3 RDT tests (13) and a study testing previously PCR tested frozen samples on 5 different RDT tests (14).…”
Section: Introductionmentioning
confidence: 99%
“…These findings, taken together with recent reports that rapid antigen tests’ performance remain consistent across variants, underscore the continued utility of rapid antigen tests. 9 With emerging reports of the BA.2 variant causing a surge in cases across the globe and in the United States, these findings hold particular importance for the public health of the country.…”
Section: Discussionmentioning
confidence: 99%